The impact of credit rating changes - Barnard, Brian (My University, 2008)
The study inquires whether ratings and rating changes in particular have any impact on bond prices. In doing so, the price data of a number of corporate vanilla bonds were investigated over corresponding rating change event periods. For various reasons, the South African Bond Market could not deliver a large sample of plain vanilla bonds that experienced a rating change. Therefore, to complement the study’s main sample, a small sample of callable corporate vanillas was also studied. In both cases the eventual sample sizes necessitated an investigation based on single issues. Neither of the samples contained “serious” rating changes; the lowest rating studied was of lower-medium investment grade quality and none of the rating changes was by more than one notch. Stationarity and unit-root tests were conducted on the non-callable and callable issues’ individual price series to determine whether the issues experienced significant price impacts in response to their respective rating-change announcements. Based on the test-results, only a number of non-callable issues experienced significant impacts. The number shrunk considerably after contamination could be proven in some cases, and when the directions of the yield spread movements were taken into consideration. An even smaller number of callable issues registered significant impacts. Contamination was not that customary in the case of callable issues, but direction of movement still played a role. Overall, out of the ten non-callable issues, none appear to have been impacted by their respective rating changes; out of the nine callable bonds, only one may have been impacted by a rating change, conditional on the issue’s call option. In some cases the rating changes were preceded by rating warnings – whether rating outlooks or rating watches; the study did not investigate whether the market responded to these warnings. The study also concludes that issue-specific characteristics play an important role in determining whether ratings can potentially impact prices. With regards to this – ii Time-to-Maturity is a good example. Additionally, it appears as if rating data should be a lot more issue-based - as opposed to being issuer-based - in order to be of any use, at least in the case of bonds that is. Under the Literature Review, enormous attention is paid to bond price determinants, the impact thereof on credit ratings, and thus the resultant ability of credit ratings to impact bond prices. The review manages to unravel the correlation between credit ratings and bond prices, to some extend. In addition, the study offers new insights into the pricing of risky bonds, particularly through an alternative modelling of default losses.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management , to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2009
Keywords: Credit rates; Bond prices; UCTD; SDG-8: Decent work and economic growth